(untitled) (Bangladesh Journal of Child Health, 2025)
Pediatric acute lymphoblastic leukemia (ALL) is the most common type of cancer in children. It accounts for 25% of all childhood cancers and approximately 80% of all cases of childhood leukemia. Understanding the clinicopathological features of pediatric ALL patients is crucial for early diagnosis, hence effective management. As pediatric leukemia is a low-prevalence disease in primary care, emergency departments, and general pediatric settings and screening strategy for identification of ALL yet to be settled, emphasis is to be given on early recognition of the disease by observing sign and symptoms of the affected children and understanding the interpretation of early CBC report. A total two hundred and twenty-three (223) children with pediatric ALL patients aged between 1-18 years who were diagnosed in the department of Pediatric Hematology and Oncology department at BSMMU from April 2018 to August 2020 were studied to identify the clinical and hematological clue for early diagnosis for the frontline physicians. The demographic characteristics of the patients, including age, gender distribution, and socioeconomic status, clinical presentation with laboratory parameters including CBC, bone marrow morphology, immunopneotyping findings were analyzed. Majority of the patients were in the age group of 1-5 years, with a slightly higher male prevalence. Fever, pallor, hepatomegaly, splenomegaly were the presenting feature in more 75% cases could be strongly considered as clinical clue for diagnosis of acute leukemia. More than 50% cases had lymohadenopathy and bony tenderness and more than 35% cases had bleeding symptoms could serve as a potential clinical clue for diagnosis of acute leukemia. Joint symptoms were present in more than 25% cases among which 6.7% cases it was the presenting symptoms accounting diagnostic delay. So it should be taken as a potential case of leukemia as differential diagnosis. Hematologic evaluation reveal decreased percentage of neutrophils for age was the constant feature present in 93.7% cases, should alert the physician for evaluation of acute leukemia.In cases of leucocytosis, it is coined with anemia, thrombocytopenia and peripheral blast giving the typical blood picture of acute leukemia.In normal leucocyte count, neutropenia was associated with anemia and or thrombocytopenia in different combination as bicytopenia with or without peripheral blast serve as diagnostic clue for acute leukemia.Pancytopenia was present at diagnosis in18.8% of cases could also be considered as clue for diagnosis of acute leukemia. BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 136-141